" ANALGESIC EFFECT OF ETHANOL EXTRACT OF CHAYOTE (Sechium Edule (Jacq.) Swartz) ON HEAT-INDUCED PAIN IN MICE (Mus musculus): " ANALGESIC EFFECT OF ETHANOL EXTRACT OF CHAYOTE (Sechium Edule (Jacq.) Swartz) ON HEAT-INDUCED PAIN IN MICE (Mus musculus) - Miseri Cordias Agape Zalukhu (Jurnal Kedokteran Methodist, 2025)
Background: Pain is a sensation that indicates that the body is experiencing tissue damage, inflammation, or more severe disorders such as nervous system dysfunction. Pain often causes discomfort such as stabbing, burning, electric shocks, and others that interfere with the quality of life of patients or people experiencing pain. Analgesics act as drugs used to reduce or eliminate pain or pain relievers without losing consciousness. Indonesia is famous for its diversity of plants, especially agricultural products and spices. One of the subtropical plants that are often found in Indonesia is the chayote plant (Sechium edule (Jacq) Swartz). where the plant can be used as an alternative medicinefor analgesics. Objective: The purpose of this study is to determine the analgesic effect of ethanol extract of chayote (Sechium edule (Jacq) Sw) on mice against heat pain.Subjects and methods: This research is an experimental laboratory study with a posttest only controlled group design on male white mice. Mice were divided into 6 groups, namely the normal group, the negative control group, the positive control group and the group given ethanol extract of chayote with a dose of 50 mg/kgBW, 100 mg/kgBW, and 150 mg/kgBW. Mice were acclimatized for 14 days first, then a hot plate test was carried out to induce pain. After themice experienced pain, they were given ethanol extract of chayote. Analgesic activity was assessed at 30, 60, 90, and 120 minutes. Results: The results of the analgesic activity of giving ethanol extract of chayote given to mice had an analgesic activity value of 7.4 ± 0.55 in the group given a dose of 100 mg/kgBW of ethanol extract of chayote where this result was the best result among the other 3 dose variants. The results of % good analgesic activity was also found in the group given 100 mg/kgBW of ethanol extract of chayote with a value of 30% compared to other groups. Conclusion: Ethanol extract of chayote 100 mg/kgBW has better analgesic activity and % analgesic activity in mice compared to other treatment groups. Keywords: Chayote, Analgesic, Hot Plate, Analgesic Activity, % Analgesic Activity